2009
DOI: 10.1002/anie.200800370
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Engineering of DNA: Molecular Beacons

Abstract: Molecular beacons (MBs) are specifically designed DNA hairpin structures that are widely used as fluorescent probes. Applications of MBs range from genetic screening, biosensor development, biochip construction, and the detection of single-nucleotide polymorphisms to mRNA monitoring in living cells. The inherent signal-transduction mechanism of MBs enables the analysis of target oligonucleotides without the separation of unbound probes. The MB stem-loop structure holds the fluorescence-donor and fluorescence-a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
381
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 606 publications
(388 citation statements)
references
References 156 publications
(245 reference statements)
3
381
0
4
Order By: Relevance
“…The hairpin is initially closed to give low fluorescence. A target DNA opens up the hairpin to increase the distance between the fluorophore and quenching, leading to signal increase [85]. Molecular beacons are attractive analytical probes since they allow for simple homogeneous assays with high sensitivity.…”
Section: Molecular Beaconsmentioning
confidence: 99%
“…The hairpin is initially closed to give low fluorescence. A target DNA opens up the hairpin to increase the distance between the fluorophore and quenching, leading to signal increase [85]. Molecular beacons are attractive analytical probes since they allow for simple homogeneous assays with high sensitivity.…”
Section: Molecular Beaconsmentioning
confidence: 99%
“…Because the sequences of aptamer probes can be custom-designed, aptamers have the particular advantage of target recognition-triggered conformational alteration, leading, in turn, to signal alteration. This strategy has been well demonstrated with molecular beacons for nucleic acid monitoring and free protein detection (22,23). Assuming that this strategy would work on surface membrane proteins of living cancer cells, we hypothesized that conformational alteration triggered by the specific binding of aptamers with cell membrane proteins could detect cancer cells, thus affording a substantial basis for the development of a unique kind of activatable molecular probe for in vivo cancer imaging.…”
mentioning
confidence: 99%
“…Moreover the use of Au based quenching has been shown to be characterised by minimal background fluorescence and subsequently improved signal-tobackground ratio (9,23,26).…”
Section: Introductionmentioning
confidence: 99%
“…The first report on the use of AuNPs as quenchers in MB and their application for the detection of specific DNA sequence was presented by Dubertret et al (19), where the authors demonstrated the possibility of replacing the quencher in a MB with AuNPs. Following this first report other authors investigated the use of MBs-AuNPs for the detection of genetic disease (12) demonstrating the ability to discriminate single point mismatches (26,30). Significant improvement in the state-of-the-art was achieved by Song et al (9) where the authors, by taking fully advantage of the quenching efficiency and scaffolding ability of AuNPs, demonstrated the possibility of having three perfectly and independently working molecular beacons immobilised on a single AuNPs highlighting the possibility of single particle multiplex detection of DNA markers.…”
Section: Introductionmentioning
confidence: 99%